Electroanalytical Performance of a Carbon Paste Electrode Modified by Coffee Husks for the Quantification of Acetaminophen in Quality Control of Commercialized Pharmaceutical Tablets - Serge Foukmeniok Mbokou; Maxime Pontié; Jean-Philippe Bouchara; Francis Merlin Melataguia Tchieno; Evangeline Njanja; Assad Mogni; Pierre Yves Pontalier; Ignas Kenfack Tonle (International Journal of Electrochemistry)
Electrochemical determination of acetaminophen (APAP) was successfully performed using a carbon paste electrode (CPE) modified with coffee husks (CH-CPE). Scanning electron microscopy (SEM) and SEM-energy dispersive X-ray spectroscopy (SEM-EDX) were, respectively, used for the morphological and elemental characterization of coffee husks prior to their utilization. The electrochemical oxidation of APAP was investigated by cyclic voltammetry (CV), differential pulse voltammetry (DPV), and square wave voltammetry (SWV). SWV technique appeared to be more sensitive since the oxidation current of APAP was twofold higher with the CH-CPE sensor than with the bare CPE, in relation to the increase in the organophilic character of the electrode surface. Furthermore, on CH-CPE, the current response of APAP varied linearly with its concentration in the range of 6.6 μM to 0.5 mM, leading to a detection limit of 0.66 μM (S/N=3). Finally, the proposed CH-CPE sensor was successfully used to determine the amount of APAP in commercialized tablets (Doliprane® 500 and Doliprane 1000), with a recovery rate ranging from 98% to 103%. This novel sensor opens the way for the development of low-cost and reliable devices for the electroanalysis of pharmaceutical formulations in developing countries.